Land-use patterns determine the distribution of soil microplastics in typical agricultural areas on the eastern Qinghai-Tibetan Plateau - Haixin, Zhang; Yimei, Huang; Shaoshan, An; Haohao, Li; Xiaoqian, Deng; Pan, Wang; Mengyuan, Fan (Journal of hazardous materials, 2022)
Land-use patterns may affect the distribution characteristics of soil microplastics (MPs), but the effects in the agricultural areas of the Qinghai-Tibetan Plateau are still unknown. This study investigated the abundance of MPs in facility, farmland, grassland, and orchard soils in the Qaidam basin and Hehuang valley of Qinghai Province and analyzed its shape, size, color, and polymer composition distribution characteristics from 105 sites. The average abundance of MPs in facility, farmland, and grassland soils in the Hehuang valley were 2795.7, 1860.5, and 910.9 items kg−1, which were 1.33, 4.84, and 1.50 times higher than those in the Qaidam basin, respectively. Orchard soils had 1322.2 items kg−1 MPs. Soil MPs abundance in grassland and farmland was positively correlated with precipitation and 0 cm ground temperature; and negatively correlated with average wind speed (p < 0.05). Both the particle size of < 1 mm and pellet-shape MPs abundance showed a positive correlation with SOC (p < 0.05). Land-use patterns had the most significant affecting force (51.35%) on soil MPs abundance (p < 0.0001). Hence, land-use patterns, regional climate, and soil properties influence the distribution characteristics of soil MPs; besides, the land-use patterns were dominant. [Display omitted] •Land-use pattern has the most significant affecting force (51.35%) on soil MPs.•Soil MP abundance in facility land is 3 times higher than in grassland.•Soil MP abundance in plastic mulching potato and maize was 4.84 times that of wheat.•Soil MP abundance in grassland is significantly decreased with increasing wind speed.•SOC content promotes the fragmentation of MPs and increases their abundance.